Structural, Docking, Molecular Dynamics and Antibacterial Analysis of Thymopentin: A Potent Anti-Cancer, -COVID-19 And Viral - Er, Alev; Çelik, Sefa; Çakır, Elif; Özel, Ayşen E.; AKYÜZ, SEVİM (Chemical Society of Ethiopia, 2025)
To gain deeper insights into the biological activity of thymopentin, its structural, anticancer, antiviral and antimicrobial properties were systematically investigated. Conformational preferences of thymopentin were investigated through conformational analysis and the lowest energy conformation was optimized using density functional theory (DFT) method, Becke three Lee–Yang–Parr (B3LYP) functional and 6-31G(d,p) basis set. Vibrational wavenumbers of the optimized structure were computed and compared with the experimental results. To elucidate the potential of thymopentin as anti-COVID-19 and anticancer agents, molecular docking simulations were performed. Thymopentin was docked into DNA (PDB ID: 1BNA), SARSCoV-2 main protease (PDB ID: 6M03) and EGFR receptor complex (PDB ID: 4HJO). Additionally, following molecular docking analyses, top-scoring ligand-receptor complexes of thymopentin with SARS-CoV-2 enzyme (6M03) and EGFR (4HJO) were subjected to 50 ns all-atom molecular dynamics (MD) simulations to examine the ligand-receptor interactions in greater detail. Moreover, the antimicrobial potency of thymopentin against the most prevailing human pathogenic microorganisms was also investigated. The strongest antibacterial activity was observed against “Listeria monocytogenes”, a pathogenic bacterium capable of causing listeriosis, a serious infection that can potentially lead to death. This study revealed the anticancer, anti-Covid 19 and antimicrobial activities of the thymopentin molecule, demonstrating its multifunctional bioactivity.
Keywords: Dft Calculations; Molecular Docking; Molecular Dynamics; Thymopentin; Vibrational Analysis